Tens to Hundreds of keV Electron Precipitation Driven by Kinetic Alfvén Waves During an Electron Injection. Issue 8 (15th August 2022) - Shen, Yangyang; Artemyev, Anton V.; Zhang, Xiao‐Jia; Angelopoulos, Vassilis; Vasko, Ivan; Turner, Drew; Tsai, Ethan; Wilkins, Colin; Weygand, James M.; Russell, Christopher T.; Ergun, Robert E.; Giles, Barbara L.
Abstract: Electron injections are critical processes associated with magnetospheric substorms, which deposit significant electron energy into the ionosphere. Although wave scattering of <10 keV electrons during injections has been well studied, the link between magnetotail electron injections and energetic (≥100 keV) electron precipitation remains elusive. Using conjugate observations between the Electron Loss and Fields Investigation (ELFIN) and Magnetospheric Multiscale (MMS) missions, we present evidence of tens to hundreds of keV electron precipitation to the ionosphere potentially driven by kinetic Alfvén waves (KAWs) associated with magnetotail electron injections and magnetic field gradients. Test particle simulations adapted to observations show that dipolarization‐front magnetic field gradients and associated ∇ B drifts allow Doppler‐shifted Landau resonances between the injected electrons and KAWs, producing electron spatial scattering across the front which results in pitch‐angle decreases and subsequent precipitation. Test particle results show that such KAW‐driven precipitation can account for ELFIN observations below ∼300 keV. Plain Language Summary: Energetic electron precipitation from magnetospheric injections has a major impact on magnetosphere‐ionosphere coupling. This energy deposition is largely in the form of electron precipitation driven by wave‐particle interactions in the magnetotail. Although wave‐driven precipitation with energies less than approximately ∼10 keV has been studied extensively, the link between energetic electron precipitation (≥∼100 keV) and electron injections remains elusive. Combining observations and simulations, this paper provides evidence of such precipitation driven by kinetic Alfvén waves, which have been previously observed to be ubiquitously associated with magnetospheric electron injections but have not been considered as an important driver for precipitation of such electrons. Key Points: Conjugate Electron Loss and Fields Investigationand Magnetospheric Multiscale observations reveal evidence of tens to hundreds of keV electron precipitation associated with kinetic Alfvén waves Dipolarized magnetic field gradients and perpendicular magnetic drifts allow Landau resonance between waves and injected electrons Adiabatic transport and spatially varying E × B and grad‐ B drifts induce perpendicular momentum scattering and electron losses